Prone Crawl Breast Couch: analysis of the translational development of a patient support device for breast cancer radiotherapy. Issue 2 (4th May 2021) - Schoepen, Max; Detand, Jan; Veldeman, Liv; Van Hulle, Hans; Vakaet, Vincent; De Neve, Wilfried
Abstract: Currently available prone support devices for breast cancer radiotherapy show different limitations, such as inconsistent patient positioning, patient discomfort and limited beam accessibility. Furthermore, medical devices tend to be developed with a top-down waterfall approach. For devices with complex use scenarios, this may impact efficacy. Therefore, we developed a patient support device with a Research through Design approach, supported by a co-design trajectory with different stakeholders. In this deductive case study, we analyze our development approach. We reflect on the NIH's T-phases of translational research and the Stanford BioDesign Process. We conclude that the user-centred and iterative aspects of our approach were beneficial to the regulatory process and the quality of the product. Furthermore, cooperating with a university hospital enhanced the regulatory process by its access to clinical data. The outcomes of this interdisciplinary research may be beneficial to other types of cancer such as lung cancer.